Strategi Sistem Informasi Giant Ekspres Swalayan dengan Metode Ward dan Peppard - Nining Ariati; Meru Hariyansa; Masito Masito; Dimas Prasetio; Dwi Revani Valepi (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
The rapid development of information technology requires companies to keep up with changes and increase operational efficiency through the use of information systems (IS). This research aims to develop IS strategic planning for Giant Ekspres Supermarkets using the Ward and Peppard method. This method includes SWOT analysis, Value Chain, Porter's Five Forces, and McFarlan's Strategic Grid to evaluate business conditions and supporting IS needs. The results of the research produced application recommendations in the form of warehouse information systems, parking security, cashiers, employee attendance and finance which are prioritized in the implementation plan for the next three years.